PCC Voltage Supported and Balanced Through MMC-DSTATCOM - XU Chen; DAI Ke; FANG Wuping; WANG Shuai (Kongzhi Yu Xinxi Jishu)
MMC-DSATCOM (modular multilevel converter based distribution static synchronous compensator) has been widely used in power quality control for distributed grids due to its advantages of fast response, high modular and easy extending structure. It analyzed the operation principle of MMC-DSTATCOM and a mathematical model was established. It realized DC capacitor voltage balance by using hierarchical control which includes averaging control, arm balancing control and individual balancing control. In order to solve the problems of PCC voltage drop and unbalance, compensation command can be obtained from PCC voltage by using two sets of inner loop controllers which include positive and negative sequence; or it can be obtained from. load current by using proportional integral(PI) controller with repetitive controller in parallel. The results of Matlab/Simulink simulation and experiment of three-phase twelve submodules prototype verify that MMC-DSTATCOM can support PCC voltage and effectively suppress PCC voltage unbalance.